Strengthening Integrated Emergency Handling as Part of Global Health Resilience - Nizamuddin Ubaidillah (Sean Institute, 2025)
Global health faces major challenges due to high population mobility, climate change, and the threats of infectious diseases and bioterrorism. Indonesia, with its strategic position, plays a crucial role in strengthening global health resilience. The Global Health Security Agenda (GHSA) serves as a key initiative to prevent, detect, and respond to cross-border health threats. The Indonesian National Armed Forces (TNI) hold a strategic role in GHSA by enhancing emergency health response centers, promoting civil-military interoperability, and fostering international collaborations with WHO, CDC, and other global organizations. Strengthening a rapid emergency response system and multisectoral coordination is essential in addressing potential pandemics and biological threats. This study highlights the importance of strengthening emergency preparedness capacity through training, infrastructure development, and adaptive policies in response to global health challenges. The findings indicate that integrating health and security approaches, along with strong international cooperation, can enhance both global and national health resilience.